Fitokimia dan Aktivitas Antiradikal DPPH Seduhan Daun Salam (Zysygium polyanthum Wight.) - Lulu Rahmatia; Nasrudin; Nurlansi (Sains: Jurnal Kimia dan Pendidikan Kimia, 2022)
Research on Phytochemicals and Antiradical Activities of DPPH infusion of Salam Leaf (Syzygium polyanthum Wight) has been carried out. This study aims to determine the phytochemical description of infusion of bay leaf (Syzygium polyanthum Wight), to determine the operating time in determining the antiradical activity of infusion of bay leaf (Syzygium polyanthum Wight) and to describe the anti-radical activity of DPPH steeped bay leaf (Syzygium polyanthum Wight). The methods used to test the secondary metabolites of bay leaf are phytochemical and anti-radical test with DPPH. A total of 5 grams of bay leaves were then extracted by infusion method with 3 repetitions in a row using water as a solvent. The filtering results were collected and the volume of bay leaf steeping was 90 mL with the extracted sample concentration of 1,264,835 ppm. The extract was then tested for Phytochemical, operating time test and anti-radical test. The results of the phytochemical test showed that the infusion of bay leaves contained flavonoids, saponins, tannins and polyphenols. The operating time test results showed that the time for the active compound in the sample and the DPPH radical to interact perfectly was at 30 minutes which gave a stable absorbance of 0.449. The results of the antioxidant activity test using the DPPH method showed that the infusion of bay leaves (Syzygium polyanthum Wigh) was classified as very weak with an IC50 value of 259.058 ppm.